Enhancing Mathematics Learning Outcomes Through The Implementation of The Problem-Based Learning Model With The Assistance of The Quizizz Application - Firnadi, Agus; Danim, Sudarwan; Herwanti, Marisha (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aimed to enhance mathematics learning outcomes by implementing the Quizizz-assisted Problem-Based Learning teaching approach. The research focused on ten first-grade students at SD Negeri 12 Bengkulu City. It employed a classroom action research design consisting of two cycles, each comprising four stages: (1) planning, (2) implementation, (3) evaluation, and (4) reflection. Research tools included observation sheets and learning achievement tests. Data analysis involved calculating averages, highest and lowest scores, score differences, and the range for each criterion using the observation sheets. Test data were analyzed by determining average scores and the percentage of students meeting the set learning criteria. The findings demonstrated an improvement in learning outcomes in each cycle. In the first cycle, the students achieved an average score of 69.44, 70% of which met the learning criteria. There was a significant enhancement in the second cycle, with an average score of 86.11 and 90% of students meeting the learning criteria. The Quizizz-assisted Problem-Based Learning model effectively enhanced student learning outcomes in mathematics for first-grade students at SD Negeri 12 Bengkulu City.